Pengaruh Online Streamer Personality, Visibility dan Efek Moderasi Usia Responden terhadap Trust to Streamer pada Live Shopping - Dhiyaa' Ayu Widaad Citra; Diah Priharsari; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Currently live shopping is very promising for businesses and UMKM because live shopping is a method of selling products by live on social media or e-commerce guided by the presenter during live shopping activities which are commonly called streamers, audiences can feel the benefits of being able to interact with streamer, buy and view products in real-time. Business actors and UMKM are also competing to carry out direct shopping activities. It's not easy for them to be able to create audience trust in streamers. There are factors that affect trust in streamers, namely Online Streamer Personality along with the moderating effect of respondent's age and Visibility. This study aims to determine the effect of Online Streamer Personality, Visibility and the moderating effect of respondent's age on trust in streamers in live shopping. This research is a quantitative study using the SEM-CB method and moderation analysis. Tests carried out in this study used IBM SPSS 22 and IBM AMOS 26 tools. Researchers distributed questionnaires to 502 respondents. The results showed that there was one hypothesis that was not accepted, namely the Visibility of Trust To Streamer.